AUTHENTIC DEED OF AUTHORITY TO SELL INDEPENDENTLY IN MAKING A DEED OF SALE AND PURCHASE - Dewa Gede Wibhi Girinatha; Nengah Renaya (NOTARIIL Jurnal Kenotariatan, 2023)
The Deed of Authority to Sell Independently is akin to a power of attorney, which grants someone the authority to act on another's behalf. In land transfers, this authorization must be made before a Notary, a public official responsible for authentic deeds and their validity, including providing copies and excerpts as per Article 15 paragraph (1) of UUJN. The purpose of this study was to study the process of making a Deed of Sale and Purchase deed using an Authentic Deed of Authority to Sell Independently and registration of the transfer of land rights based on an Authentic Deed of Authority to Sell Independently at the Land Office. The research method used is the normative research method. The results of this study showed that the Authentic Deed of Authority to Sell Independently can be used in making a sale and purchase deed if it meets the specified conditions. In addition, the Authentic Deed of Authority to Sell Independently can also be used in registering the transfer of land rights at the Land Office.